Recent trends and future prospects of cross-border agricultural trade in Niger - Odjo, Sunday P.; Badiane, Ousmane (Wageningen Academic Publishers, 2018)
High rainfall variability, resulting in frequent floods, droughts and locus infestations, undermines Niger’s efforts to ensure its food security. This paper deals with the role of regional trade in fostering the resilience of domestic food markets in Niger. Current trends in agricultural trade between Niger and its regional neighbours reveal that the regional market plays a crucial role in stabilising domestic supplies of staple food crops, in addition to serving as the major export outlet for Niger’s cash crops and live animals. An economy-wide multimarket and multi-country model of the West Africa region is used to explore likely changes in cross-border trade flows. Assuming a continuation of current trends in cultivation areas, crop yields, population and nonagricultural income, the projection of future prospects of cross-border agricultural trade reveals that Niger’s participation in regional trade will continue to expand both in terms of net imports and exports. Simulation results suggest that the level of participation in the future could be affected considerably by potential changes in policy and productivity such as a modest reduction in general trading costs, the removal of cross-border trade obstacles, or a slight increase in yields. Such policy changes would have important implications not just for the country’s trade with the rest of the region but also for it ability to improve food security for its population.